Evaluation of in vitro antagonistic activity of fungi from peatlands against Ganoderma species under acidic condition - SUPRIYANTO; PURWANTO; S.H. POROMARTO; SUPYANI (Society for Indonesian Biodiversity, 2020)
Abstract. Supriyanto, Purwanto, Poromarto SH, Supyani. 2020. Evaluation of in vitro antagonistic activity of fungi from peatlands against Ganoderma species under acidic conditions. Biodiversitas 21: 2935-2945. The use of peatlands is a significant contributor to the world’s palm oil production. A serious problem of oil palm plantations in peatlands is the high incidence of basal stem rot (BSR) disease caused by Ganoderma, which has a higher attack rate than on mineral soils. There is no effective way to control Ganoderma in peatlands. At present, the effort for the same focuses on environment-friendly biological methods; however, this is constrained by the unavailability of appropriate biological agents for peatlands. The development of biological control agents for peatlands is hampered by limited data on biological control of Ganoderma in peatlands. This research was conducted to evaluate the in vitro antagonistic activity of fungi isolated from a peatland in acidic pH conditions. Twenty-seven Ganoderma-antagonistic fungi from peatland were evaluated for their activity and their ability to antagonism in vitro within a pH range of 2-7. The results show that most antagonistic fungi from peatland, based on biomass weight, the sporulation ability, and germination of conidium, were able to grow optimally at pH 3.0-4.0, indicating that most of the Ganoderma-antagonistic fungi from peatland can be used as biological control agents for BSR on oil palms in peatlands.